Trends, global comparisons, and projections of early onset colorectal cancer burden in China based on GBD study 2021 - Shun Seng Ong; Lianjie Xu; Xiaoyue Deng; Hai Lu; Tianshu Xu (Scientific Reports)
Abstract This study aimed to analyze the trends of early-onset colorectal cancer (EOCRC) among individuals aged 15 to 49 in China from 1990 to 2021 and compare them with global patterns using data from the Global Burden of Disease (GBD) study. The analysis focused on age-standardized incidence rates (ASIR), prevalence rates (ASPR), mortality rates (ASMR), and disability-adjusted life years (DALYs). Joinpoint regression was used to determine the average annual percentage change (AAPC), and the ARIMA model was employed to forecast trends from 2022 to 2050. Results showed a significant increase in ASIR and ASPR in China, with a more rapid rise compared to global trends. ASMR and DALYs showed a decline, indicating improved survival rates. However, the increasing DALYs in China suggest a growing health impact. The ARIMA projections indicate a continued increase in EOCRC burden in China, highlighting the need for enhanced prevention and early detection strategies. This study underscores the necessity for intensified public health interventions to address the rising incidence of EOCRC in China.